Short communication: The global health community needs to start planning for the impact of the climate crisis on maternal and newborn health - Skye Wheeler; Elena Ateva; Robyn Churchill; Elizabeth Pleuss; Betsy McCallon; Andrew Storey; Muhammad Ihatsham Akram; Maria Teresa Carpio; Yogan Pillay; Olufunke Fasawe (Elsevier, 2022)
The climate crisis will worsen already high rates of maternal and newborn mortality and adverse birth outcomes, exacerbating existing inequities between and within countries. Governments should consider beginning plans for responses now, engaging with partners such as national and international non-governmental organizations, local civil society groups, the private sector and donors, and the wider global community, to commence implementation of relevant policy and health service delivery measures while accelerating ongoing efforts to better improve maternal and newborn health.